2012
DOI: 10.1038/eye.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetic retinopathy in Chongqing pre-diabetes patients

Abstract: Purpose To investigate the prevalence of diabetic retinopathy (DR) and relative risk factors among Chongqing pre-diabetes patients. Methods A total of 750 participants were recruited in this cross-sectional study. All participants underwent a complete physical examination and an oral glucose-tolerance test. In all, 110 of the 125 newly diagnosed pre-diabetics and their healthy spouses as controls were examined with fluorescence fundus angiographies, and their blood with biochemical analyses. All the pre-diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…12 Rough estimates show that for every diabetic patient, there are three prediabetic patients aged ≥ 20 years in the US. 13 Although the relationship of other co-morbidities such as neuropathy and retinopathy in prediabetic state has been vastly studied, [14][15][16][17][18][19] the picture of musculoskeletal involvement in this phase has been less clearly drawn. The nature, prevalence and the determinant factors of musculoskeletal manifestations in diabetic and prediabetic patients have not yet been studied in detail in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…12 Rough estimates show that for every diabetic patient, there are three prediabetic patients aged ≥ 20 years in the US. 13 Although the relationship of other co-morbidities such as neuropathy and retinopathy in prediabetic state has been vastly studied, [14][15][16][17][18][19] the picture of musculoskeletal involvement in this phase has been less clearly drawn. The nature, prevalence and the determinant factors of musculoskeletal manifestations in diabetic and prediabetic patients have not yet been studied in detail in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably the reason why in the study by Bahar et al (9), the risk of microalbuminuria which is a marker for atherosclerosis and coronary artery disease, is already high in IFG and IGT subjects. Similarly, retinopathy is found in 20.91% of IGT patients (10). Since insulin determination is not routinely done in the workup of highrisk individuals, beginning impairment of metabolic activity as evidenced by elevated insulin level would likely be missed out.…”
Section: Discussionmentioning
confidence: 99%
“…Since insulin determination is not routinely done in the workup of highrisk individuals, beginning impairment of metabolic activity as evidenced by elevated insulin level would likely be missed out. Therefore, at the level of IFG and IGT, complications common in established diabetes are already seen (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…10 In Scotland, the comparable figures were 67% for men and 62% for women. 11 The prevalence of obesity (BMI 30+) is similar among men and women, but men are more likely to be overweight (BMI [25][26][27][28][29][30]. A large study of people with diabetes in Scotland found that men are more likely than women of a similar age to develop diabetes at a lower BMI, with the BMI 'gap' between men and women most significant at younger ages.…”
Section: Risk Factorsmentioning
confidence: 99%
“…24 Men also tend to have more severe retinopathy at the time of type 2 diagnosis, and there is evidence that retinopathy can be present at the prediabetes stage. 25 However, menand particularly younger men -with a diabetes diagnosis are less likely than women to seek routine eye checks 26 or respond to invitations to attend diabetic retinopathy screening. 27 ED is a common problem among men who have diabetes, affecting 35-75%.…”
Section: Sequelaementioning
confidence: 99%